IADC/SPE Drilling Conference 1994
DOI: 10.2118/27461-ms
|View full text |Cite
|
Sign up to set email alerts
|

Designer Directional Drilling to Increase Total Recovery and Production Rates

Abstract: SPE and IADC Members Abstract The implementation of a new type of well profile. the designer profile, has resulted in increased recovery and production rates. The geologically complex Gullfaks Field (See fig. 1), located in the Norwegian sector of the North Sea, has seen significant change in the initial field development plan (FOP) as a result of the design technology. A new type of well profile was necessary to increase both total recovery and production ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

1994
1994
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…liner was run in hole with an 8 1 =4-in. reamer shoe to enable the liner to be worked down with rotation (Eck-Olsen et al 1994, 2007Alfsen et al 1995;Hjelle et al 2006). The actual torque values in the open hole showed that rotating the liner was impossible.…”
Section: Well Designmentioning
confidence: 99%
“…liner was run in hole with an 8 1 =4-in. reamer shoe to enable the liner to be worked down with rotation (Eck-Olsen et al 1994, 2007Alfsen et al 1995;Hjelle et al 2006). The actual torque values in the open hole showed that rotating the liner was impossible.…”
Section: Well Designmentioning
confidence: 99%
“…It has been reported that hole cleaning is critical to the success of extended reach drilling, especially where the hole inclination is high 9,12,14,15,16 . A lot of work has been done on the improvement in hole cleaning with drillstring rotation 11,12,16,17,18,19 .…”
Section: Theoretical Benefits Of Srdmentioning
confidence: 99%
“…The trajectory is shown as a dashed line, and it changes course to follow the pay sand. This type of trajectory is sometimes called a designer well 17 • These well paths cannot easily be made with current directional drilling software but must use newer plan by section methods. Plan by section paths are characterized by sets of build/drop/tum segments followed by a tangent or hold segment.…”
Section: The Rea(; Time Geological Structure Evaluationmentioning
confidence: 99%